Implementing gamification to develop B2 level learnersʼlinguistic competence (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores the use of gamification as an instructional strategy to enhance linguistic competence among B2-level English language learners. By integrating game-based elements such as points, leaderboards, badges, and narrative missions into language instruction, educators can foster engaging and motivational learning environments that promote active participation. The study reviews literature on gamification in second language acquisition and evaluates its impact on vocabulary acquisition, grammar proficiency, communicative competence, and learner motivation. Data were collected from classroom interventions, supported by surveys and language assessments. The findings indicate that gamified learning significantly boosts engagement and yields measurable improvements in linguistic skills. The article concludes with recommendations for effectively integrating gamification into B2-level language curricula.